Innovations for models of admission Study of cases and inclusion strategies in higher education - Mainieri Hidalgo, Aida María (2017)
This scientific paper presents one research that bears the same name. It was done under the University of Costa Rica Scholastic Aptitude Test Program. While college admission models in the international context have been kept since their origins with updates that try to improve excellence and equity, Universities that serve populations with greater cultural and socioeconomic diversity, have recently incorporated programs that respond to the demand points each again human rights. The debate on issues of selecting and evaluating, new technologies and styles of adequacy, has to include several policies and practices that are fundamental. The focus of attention are the minority groups with lack of opportunities, whose reality is constituted by educational and socio-cultural disadvantages and those aspects influence the enrollment in ES, and in this groups’ talent is distributed a wide range of shades. So, it was proposed to look for novel strategies of inclusion, based on the ethics of fairness and justice. The research was performed by an exploratory approach, with case studies. It started with a literature and documentary review for the formulation of a general framework, essential for identification of the cases; open and in-depth expert interviews are incorporated, in addition to field observation and participation. Case studies in Latin America: Chile and Argentina in comparison to Costa Rica, as well as China, report innovative strategies and their possible incorporation into the processes of this institution with potential transformative impact in society.